A Simulation study of availability analysis on a chemical process industry considering spare part inventory. (December 2019) - Salsabila, N Y; Siswanto, N
Abstract: A maintenance strategy is an important factor in the production activities of the process industry. Since the process industry consists of many components, the failure mode is relatively complex. This paper observes one of the petrochemical companies in Indonesia which produces Pythalic Anhydride. The company is able to produce in 20.69 days every month. In reality, during 2017, the company produced 23 days every month on average. Production, known as the calendar day, which cannot achieve the target can affect customer service level. This research focuses on evaluating availability in order to minimize Mean Time to Repair (MTTR). One of the best strategies is to control the spare part inventory policy so that the spare part must be available when an equipment downtime occurs. We will use two modeling techniques to solve the problem: (a) reliability block diagram will be used to model the failure mode and (b) the simulation model will be used to model the entire system, including random variables and variable inter-dependency. After conducting scenario analysis by varying some parameters, the availability increased to 91.8% and average calendar days decreased to 22.64 days per month.